Conductive magnetite nanoparticles trigger syntrophic methane production in single chamber microbial electrochemical systems. (January 2020) - Vu, Mung Thi; Noori, Md Tabish; Min, Booki
Graphical abstract: Highlights: Methanogenesis in MES was significantly enhanced with magnetite nanoparticles. Magnetite nanoparticles promoted current generation, substrate and VFAs removal. Overpotential losses of MES was decreased with magnetite nanoparticles addition. Magnetite may act as electrical conduit for extracellular electron transfer. Abstract: Performance of methane-producing microbial electrochemical systems (MESs) is highly reliant on electron transfer efficiency from electrode to microorganisms and vice versa. In this study, magnetite nanoparticles were used as electron carriers to enhance extracellular electron transfer in single chamber MESs. The MES with magnetite exhibited the highest methane yield and current generation of 0.37 ± 0.009 LCH4 /gCOD and 9.6 mA, respectively among the tested reactors. The experimental data was observed to be highly consistent with modified Gompertz model results (R 2  > 0.99), which also showed 74.2% and 22.1% enhanced methane production rate in MES with magnetite as compared to control AD and MES without magnetite, respectively. Cyclic voltammetry and electrochemical impedance spectroscopy analysis confirmed that magnetite enhanced catalytic activity of biofilm and lowered both solution and charge transfer resistance. Therefore, supplementing magnetite in MESs could be a strategy to develop an efficient syntrophic biomethanation in field scale applications.